JOYFUL LEARNING AS A STRATEGY TO ENHANCE COGNITIVE LEARNING OUTCOMES IN ISLAMIC RELIGIOUS EDUCATION - Hakim, Ramadhani Firman; Fitriana, Dyah Ayu; Jaya, Arim Irsyadulloh Albin (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study examines the effectiveness of Joyful Learning as a pedagogical strategy to enhance students’ cognitive learning outcomes in Islamic Religious Education (PAI) at MTs Salafiyah Ngaringan, a pesantren-based junior high school in Central Java. Using a posttest-only control group quasi-experimental design with 50 eighth-grade students, the experimental class received PAI instruction through Joyful Learning activities—role-play, group discussion, and interactive quizzes—while the control class followed conventional teaching. Independent t-test results revealed a significant difference (p = 0.000), with the experimental group (M = 83.72) outperforming the control group (M = 72.88). These findings indicate that Joyful Learning effectively increases students’ cognitive achievement by fostering engagement, motivation, and contextual understanding. The novelty of this study lies in its implementation within a traditional pesantren-based school, demonstrating that pedagogical innovation can succeed even with limited resources. This research contributes to Islamic education reform by promoting learner-centered, joyful, and contextually responsive instruction. Penelitian ini menelaah efektivitas strategi Joyful Learning dalam meningkatkan hasil belajar kognitif siswa pada mata pelajaran Pendidikan Agama Islam (PAI) di MTs Salafiyah Ngaringan, sebuah madrasah berbasis pesantren di Jawa Tengah. Dengan menggunakan desain kuasi-eksperimen posttest-only control group terhadap 50 siswa kelas VIII, kelompok eksperimen diajar melalui aktivitas Joyful Learning seperti simulasi, diskusi kelompok, dan kuis interaktif, sedangkan kelompok kontrol menggunakan metode konvensional. Hasil uji t independen menunjukkan perbedaan signifikan (p = 0,000), di mana kelompok eksperimen (rata-rata = 83,72) melampaui kelompok kontrol (rata-rata = 72,88). Temuan ini membuktikan bahwa Joyful Learning efektif meningkatkan capaian kognitif melalui peningkatan motivasi, keterlibatan, dan pemahaman kontekstual. Kebaruan penelitian ini terletak pada penerapannya di madrasah salafiyah tradisional yang minim fasilitas, namun mampu menghasilkan inovasi pedagogis yang bermakna. Penelitian ini berkontribusi pada pembaruan pendidikan Islam melalui pembelajaran yang berpusat pada siswa, menyenangkan, dan responsif terhadap konteks lokal.